Effect of Deficit Irrigation on the Morphological Quantitative Traits of Anise (Pimpinella anisum L.) (Damascus University Journal of agriculture sciences, 2021)
This study was conducted in order to estimate the effect of deficit irrigation on morphological and quantitative traits of anise under three irrigation treatments (60,70 and 80% out of full irrigation respectively). Result showed that full irrigation treatment was significantly superior compared with all deficit irrigation treatments in all the investigated morphological traits, while physiological observation of the plant indicated to differences in the crop growing period. The longest crop growing period was in the full irrigation treatment whereas it gradually decreased with the deceasing of the amount of water applied.
Keywords: Anise (Pimpinella anisum L.); Deficit irrigation; Morphological traits